Constraints in Implementing Decentralisation in Zambia - Tembo, Moffat; Mwanaumo, Erastus Misheng’u (International Journal of Scientific Research and Management (IJSRM), 2022)
Purpose: Against a backdrop of Zambia’s continued weak economic conditions and with many local authorities, experiencing declining local revenues and financial performance, this paper presents a synthesis of the local government turnaround findings. It aims to identify the constraints to decentralization and recovery strategies based on the evidence provided by pragmatic research.Design/methodology/approach: The questionnaire survey was carried out over a period of two weeks from sixth to 20 May 2019. 120 questionnaires were distributed via online to all 120 respondents using purposive and critical case sampling. The questionnaire was created and deployed using free online software (kobotoolbox) to the 120 critical case and purposively selected respondents. Out of 120 respondents 103 responded creating a survey response rate of above 85%.Findings: The research found that the major constraints in implementing decentralisation included; Continued delay to release decentralised functions by central government; lack of political will from central government; failure to implement the agreed decentralised structure by central government; failure to relinquish some revenue streams to local authorities; governments unclear policy guidance on decentralization; lack of a standardised system as well as a monitoring mechanism; and failure to generate adequate own revenue by local authorities.Research implications: This research assumes a significant role in formulation of policy for local government tier and could provide a basis for further research in this area as well as designing policies for an improved local government fiscal system.Practical implications: this study adds pragmatic perspectives towards resolving revenue problems faced by Zambia’s local authorities.Originality/value: This paper compiles facts and offers practitioners an evidence-based view through investigating Zambia’s local government economic structure, analyzing forces underlying them and examining their consequential cultural interplay.Keywords: Decentralisation; Local Authority; Local Revenue